Direct impact of mindset on reading-based outcomes in upper elementary students with reading difficulties - Stanley, Christopher; Heo, Jungyeong; Petscher, Yaacov; Al Otaiba, Stephanie; Wanzek, Jeanne (Frontiers in Education, 2023)
Mindset involves an array of beliefs related to the malleability of certain attributes, including intelligence. One's growth mindset comprises a variety of cognitive and motivational factors (e.g., learning goals, effort beliefs) and the perception that skill attainment and outcome in any domain are tethered to personal effort. A fixed mindset encompasses goals, beliefs, and perceptions that skill level is not malleable or impacted by effort. Structural equation models tested investigated direct and indirect pathways of mindset and motivational variables (i.e., learning goals, effort beliefs) with reading outcomes (i.e., word reading, fluency, reading comprehension) in a diverse sample of fourth grade students (n = 408) with reading difficulties. Results revealed a direct impact of fixed mindset (-.21 to -.36) and effort beliefs (.18 to .31) on all standardized, reading-based outcomes. There were no significant mediating pathways. Results are juxtaposed to other research in this area, and practical implications are discussed. Growth mindset appears a robust predictor of positive academic outcomes, and it may be beneficial to facilitate growth mindset in classrooms.